Advances in Information Storage Systems, Volume 7 - Bhushan Bharat (Worl Scientific, 1995)
This text is part of the series "Advances in Information Storage Systems". It covers a wide range of interdisciplinary technical areas, related to magnetic or optical storage systems. Topics covered by the series include: friction; adhesion; wear and lubrications; coatings; solid mechanics; air flow; contamination; instrumentation; dynamics; shock and vibration; controls; head and suspension design; actuators; spindle and actuator motors and bearings; structure of thin films; corrosion; long-term reliability; materials and processing; manufacturing and automation; and economics. This volume contains 30 articles covering various aspects of the information storage and processing industry. It is organized into three parts: mechanics and tribology of magnetic rigid disk drives; dynamics and controls of magnetic rigid disk drive; and mechanics of flexible media systems.